2011
DOI: 10.2341/11-018-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorhexidine Pretreatment on Bond Strength Durability of Caries–affected Dentin Over 2-Year Aging in Artificial Saliva and Under Simulated Intrapulpal Pressure

Abstract: Pretreatment of caries-affected dentin with 5% chlorhexidine decelerates the bond strength loss over the long term. SUMMARYObjective: To evaluate the influence of 2% and 5% chlorhexidine (CHX) pretreatment on bond durability of a self-etching adhesive to normal (ND) and caries-affected (AD) dentin after 2-years of aging in artificial saliva and under simulated intrapulpal pressure (IPP).Methods: One hundred twenty freshly extracted carious teeth were ground to expose ND and AD. Specimens were distributed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 48 publications
(59 reference statements)
7
45
0
3
Order By: Relevance
“…Our results corroborate those of previous studies 9,10 reporting that disinfection did not adversely affect bonding to dentin compared with a control group. Nevertheless, these results do not agree with earlier reports showing decreased bond strengths when self-etch adhesive systems were applied after CHXbased cavity disinfectant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results corroborate those of previous studies 9,10 reporting that disinfection did not adversely affect bonding to dentin compared with a control group. Nevertheless, these results do not agree with earlier reports showing decreased bond strengths when self-etch adhesive systems were applied after CHXbased cavity disinfectant.…”
Section: Discussionsupporting
confidence: 92%
“…6 However, the scientific literature reports conflicting results, since in vitro studies have demonstrated decreased bond strengths with self-etch adhesive systems applied after CHX-based cavity disinfectant, [7][8][9] while analysis of other data [9][10][11] demonstrated no adverse effect on dentin bonding compared with a control group. In the most commonly encountered clinical situations, especially when a cavity disinfectant is applied, bonding procedures are carried out in abnormal dentin, such as caries-affected dentin.…”
Section: Introductionmentioning
confidence: 99%
“…77,96,97,98,99 Higher bond strength durability of a two-step self-etch adhesive over 2-year aging in artificial saliva and under simulated intrapulpal pressure was also described in the literature when caries-affected dentin was pretreated with CHX. 100 Besides, the degradation of the adhesive interface in primary teeth may be counteracted or blocked by the application of CHX as a therapeutic primer. 92,101 Avoiding to add another step in the adhesive treatment of dentin, 6,88 some investigators have studied the beneficial effects of incorporation CHX into the etchant 83,84 or the adhesive.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…Output light intensity (!500 mW/cm 2 ) was periodically checked using an LED radiometer (Kerr Dental Specialties, West Collins Orange, CA, USA). The specimens were left to stand for 15 minutes and then were immersed in artificial saliva 17 for one month at 378C.…”
Section: Substrate Specimen Preparationmentioning
confidence: 99%